The RNA Polymerase II Core Promoter in Drosophila - Vo Ngoc, Long (Genetics, 2019)
Transcription by RNA polymerase II initiates at the core promoter, which is sometimes referred to as the “gateway to transcription.” Here, we describe the properties of the RNA polymerase II core promoter in Drosophila. The core promoter is at a strategic position in the expression of genes, as it is the site of convergence of the signals that lead to transcriptional activation. Importantly, core promoters are diverse in terms of their structure and function. They are composed of various combinations of sequence motifs such as the TATA box, initiator (Inr), and downstream core promoter element (DPE). Different types of core promoters are transcribed via distinct mechanisms. Moreover, some transcriptional enhancers exhibit specificity for particular types of core promoters. These findings indicate that the core promoter is a central component of the transcriptional apparatus that regulates gene expression.